Effect of Goading on the Performance of Bullocks in Team Work - Dubey, U C; Chauduhri, Deepak (Journal of Agricultural Engineering, 2006)
Multi-pair of animals are used in team work for operation of single mould board plough for deep ploughing in the black/hard soil. Two/three pairs were hitched in team with CIAE animal loading car and the bullock pairs were arranged in series as per their decreasing body weight to assess the draftability of animals in team under the varying load and goading conditions. The load on two and three pairs was varied from 4.81- 12.5 % and 5.56 -8.74 % respectively of their combined body weight with CIAE animal loading car. When two pairs of bullocks were used, the front pair exerted a greater pull as compared to the rear pair. The difference of draft in terms of percentage of body weight ranged from 0.01 - 3.48 % depending upon load and type of goading. The front pair exerted 0.79 to 1.31 % higher draft (in percentage of body weight) as compared to average and rear pair 1.0-1.66 % less draft. When three pairs of animals were used, the pull exerted by front and middle pairs was higher compared to rear pair. Difference in draft in terms of percentage of body weight between the pairs ranged from 0.07-6.14 % depending upon load and goads conditions. The front pair exerted a greater pull in terms of percentage body weight as compared to average pull. The middle pair exerted pull close to average value of pull of front and rear pair whereas rear pair exerted lesser pull as compared to average pull. In both two and three pairs of animals, rear goading gave minimum difference in pull between pairs in terms of percentage body weight. However the average difference in case of three pair of animals was 57 % of that observed in case of two pair of animals. Thus, use of three pairs of animals with rear pair goading gave best result.